Komunikowanie na forum w trójwymiarowym systemie percepcji zmysłów = Communication on the forum in a three-dimensional sensory perception system - Postawa, Andrzej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of this work is the analysis of posts on online forum in a three-dimensional system of perception of the senses. The first dimension of this system is the figurative message information, the second ? audial communication, the third coordinate creates the somatosensorial-gustatory-olfactory-vestibular system. By assigning the first coordinate the color blue, the second ? red, and the third ? yellow, we can get a color image expression not only in English but in any natural language.
Keywords: tożsamość; tożsamość aktywna; tożsamość pasywna; tożsamość deliberatywna; memetyka; identyfikacja; samoidentyfikacja; język; językoznawstwo; językoznawstwo polskie